2020
DOI: 10.3390/app10248906
|View full text |Cite
|
Sign up to set email alerts
|

New and Emerging Risk Factors in Occupational Health

Abstract: Workplace health and safety is constantly evolving both in developed and developing countries. Under the tumultuous development of technology, working environments are changing, leading to the onset of new occupational hazards and unprecedented risk conditions deriving from the new ways of organizing work. At the same time, progress in medical science, with the knowledge in the fields of genetics, metabolomics, big data, and smart technologies, makes it possible to promptly identify and treat risk conditions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…28,29 Besides, following the practices of advanced countries, occupational health surveillance should be implemented in the workplace setting, especially to tackle the negative impact of the COVID-19 pandemic. 30,31 Awareness projects or seminars could be arranged in the future related to EI and its importance in promoting the psychological well-being of medical health workers. These seminars could be advertised to encourage the doctors to attend them.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Besides, following the practices of advanced countries, occupational health surveillance should be implemented in the workplace setting, especially to tackle the negative impact of the COVID-19 pandemic. 30,31 Awareness projects or seminars could be arranged in the future related to EI and its importance in promoting the psychological well-being of medical health workers. These seminars could be advertised to encourage the doctors to attend them.…”
Section: Discussionmentioning
confidence: 99%
“…An occupational hazard is an injury or ailment resulting from the work one does or from the surrounding in which one works [ 54 , 55 , 56 ]. The consequences of workplace hazards could be trauma, even post-traumatic stress disorder (PTSD), loss of dignity, anxiety, depression, attempt at suicide, decreased self-esteem, lack of trust in people, premature aging, losing autonomy, injuries, absenteeism, and physical and musculoskeletal injuries [ 57 , 58 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…All these may lead to increasing occupational stress of the grass-roots civil servants. Many kinds of research have shown that career stress could induce physical illness and some psychological problems [8][9][10]. For grass-roots civil servants, stress threatens their health and the work efficiency of the government and social stability.…”
Section: Introductionmentioning
confidence: 99%